(untitled) (LACCEI, 2024)
This study presents a comparative analysis of two structural design concepts in the Ecuadorian construction market: hidden vs. drop beams. Typical structural systems used in low-rise buildings are special-moment frames, with either hidden or drop beams. The former is preferred by contractors and builders due to a notion of affordability, despite strong evidence of such system collapsing during recent earthquake events, particularly the April 2016 Ecuador earthquake (M7.8). This comparative analysis spans the mechanical, seismic, and economical aspects. A total of 32 structural models are developed and analyzed for linear and nonlinear static and dynamic response. Sixteen of these models are structures containing hidden beams, and the remaining 16 contain drop beams. The results show that structures with drop beams have no significant cost differences with hidden beams, while achieving a noticeable better structural behavior in high-risk seismic zones. The research gap that the present work aims to fill is a noticeable lack of previous studies comparing these two construction systems.